OVERCOMING CHALLENGES IN IMPLEMENTING MODERN METHODOLOGY IN FOREIGN LANGUAGE TEACHING - Maxmudxo’jayeva Nasibaxon Azim qizi,; Barno Ziyatova, (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article explores the major challenges faced when implementing modern methodologies in foreign language teaching and proposes practical solutions supported by international research. It discusses problems such as the persistence of outdated  methods,  insufficient  teacher  training, inadequate  technological  resources, low learner motivation, and institutional constraints. Drawing on recent studies, the paper  argues  that  overcoming  these  barriers  requires  a  comprehensive  approach involving  curriculum  reform,  teacher  professional  development,  technological investment,  motivational  strategies,  and  institutional  support.  These  measures  are essential for aligning foreign language education with global communicative needs.